Medicinal applications of d-ribose l-cysteine in neuro-endocrinopathy, reproductive dysfunction and cardio-metabolic syndrome: A review of evidence in animal investigations - Oyovwi Mega Obukohwo; Falajiki Yewande Faith; Ohwin Peggy Ejiro; Mok Mishael Onyebuchi; Ayodeji Folorunsho Ajayi (Elsevier, 2024)
In recent years, the emergence of d-ribose l-cysteine (DLRC) as a potential treatment regimen for neuro-endocrinopathy, reproductive dysfunction and cardio-metabolic syndrome has been gaining attention among medical professionals. This review discusses the safety issues associated with d-ribose l-cysteine and its potential in treating neurological damage, reproductive dysfunction, endocrine diseases, Chondrocyte degeneration, and cardio-metabolic syndrome. Electronic databases were searched for information on d-ribose-l-cysteine and its potential effects on neuroendocrine disorders, using various search terms. In vitro and in vivo studies were examined for any links between d-ribose-l-cysteine and neuroendocrine protection. This review seeks to analyze the available evidence for such a treatment regimen, with particular emphasis on its efficacy, safety profile, and limitations. A review of preclinical studies related to d-ribose l-cysteine and the aforementioned conditions was conducted. The studies demonstrate that the treatment is safe as well as demonstrates promising results in terms of efficacy. This review provides an overview of available evidence for the use of d-ribose l-cysteine as a potential treatment option for neurological damage, reproductive dysfunction, endocrine diseases, Chondrocyte degeneration, and cardio-metabolic syndrome, providing a rationale for further investigation into this therapy. DRLC plays an important role in neuroendocrine and reproductive functions as well as cardiometabolic functions in animal model. Its assessment provides essential information that could guide treatment strategies aimed at improving male reproductive potential. Taken together, these recent advances highlight a future therapeutic intervention in assessing male physiological functions.